Four New Xanthones from Cratoxylum cochinchinense and Their In Vitro Antiproliferative Effects - Ito, Chihiro; Matsui, Takuya; Niimi, Ai; Tan, Hugh T.-W.; Itoigawa, Masataka (Planta Medica, 2017)
The study of the chemical constituents of branches and twigs of Cratoxylum cochinchinense collected in Singapore led to the isolation and structural elucidation of four new xanthones, named cratoxanthone A (1), B (2), C (3), and D (4), together with six known xanthones (5–10) and one known dihydroanthracenone (11). Eight xanthones (including 1 and 2) and 11 were tested for their antiproliferative activity in three human carcinoma cell lines (lung adenocarcinoma A549, colorectal carcinoma Colo205, and epidermoid carcinoma KB) and a human acute lymphoblastic leukemia B cell line (NALM-6), and the mitochondrial membrane potential was determined in KB cells. New xanthones 1 and 2 attenuated NALM-6 cell proliferation with IC50 values of 17.78 and 8.27 µM, respectively. Furthermore, KB cells treated with these compounds had significantly decreased mitochondrial membrane potentials. Notably, the proliferation of A549 cells was specifically inhibited by 11, but not the xanthones.
Keywords: Cratoxylum cochinchinense; Hypericaceae; xanthones; dihydroanthracenone; antiproliferative activity